A Diagnostic Dilemma Upon Discovery of a Left Ventricle Mass: A Case Report - Hedieh Alimi; Ali Tajik (Clinical Case Reports)
ABSTRACT Left ventricular mass is an uncommon condition, with thrombus being the most frequent cause. In this report, we present a complicated case of a cardiac mass (a left ventricular mass) and provide educational insights on distinguishing between cardiac tumors and left ventricular thrombus, using imaging modalities like echocardiography.